THE RESEARCH FOUNDATIONS OF VOLODYMYR DERZHAVYN’S SCIENTIFIC THINKING - Хороб, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article makes an attempt to reveal the research foundations of scientific thinking of the famous scholar from the Ukrainian Diaspora Volodymyr Derzhavyn. On the example of his many works of a theoretical-methodological and historical-literary direction, numerous studies into Ukrainian and foreign belles-lettres that the Ukrainian literary critic wrote in the post-war years, the dominant concepts of his research toolkit are defined.